FISCAL AND MONETARY POLICY SYNERGY IN THE FRAMEWORK OF ISLAMIC ECONOMICS: SOLUTIONS TO MACROECONOMIC STABILITY CHALLENGES - Alifah, Nurul; Permana, Haiqkal; Ajrika, Naela; Aziz, Abdul; Rosviana, Mohammad Irfan (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2025)
This research aims to obtain the results of a synergy analysis of fiscal and monetary policies within the framework of Islamic economics: solutions to the challenges of Islamic macroeconomic stability. The research method uses a qualitative approach, field data collection uses analytical techniques, reading, summarizing and selecting material. To understand the data we take from various journals by researching and reading carefully. Synergy between fiscal and monetary policies is a key element in achieving sustainable economic stability, especially in the context of countries that apply Islamic economic principles. Within this framework, both policies not only aim to achieve economic growth, but also to ensure social justice and societal welfare. Fiscal policy, which includes government spending and taxation, functions to manage resources and support programs that benefit society. The research results show that in the context of macroeconomics, another important economic fundamental is government fiscal policy. Monetary strategy for Fiscal policy in Macroeconomics, namely the implementation of fiscal policy and monetary policy carried out by these two different institutions must not conflict with one another, where both must mutually adjust the policies they make. To maintain national stability in the economic sector, the government needs to keep the inflation rate from exceeding 5%. One of the government's efforts to overcome this inflation problem is by implementing fiscal policy and monetary policy.